Implementation of Innovative Technologies in Inventory Management in Cotton-Textile Clusters - Bakhtiyor Nasimov (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
The article analyzes the application of innovative technologies in inventory management within cotton-textile clusters (CTCs). The study highlights the significance of efficient inventory planning for ensuring uninterrupted production processes, optimizing costs, and meeting market demand. The work examines domestic and international experiences in inventory management, as well as the impact of digitalization, monitoring systems, and modern logistics on production efficiency. The research also presents forecasts under inertial and innovative development scenarios, emphasizing the potential growth of cotton yield, production volumes, and exports by 2030. The findings provide practical recommendations for enhancing the competitiveness of Uzbekistan’s cotton-textile industry through the introduction of advanced technologies in inventory and resource management.